Effects of whey protein and dietary fiber intake on insulin sensitivity, body composition, energy expenditure, blood pressure, and appetite in subjects with abdominal obesity - Fuglsang-Nielsen, Rasmus; Rakvaag, Elin; Langdahl, Bente; Knudsen, Knud Erik Bach; Hartmann, Bolette; Holst, Jens Juul; Hermansen, Kjeld; Gregersen, Søren (European journal of clinical nutrition, 2021)
Background Recently, we demonstrated that whey protein (WP) combined with low dietary fiber improved lipemia, a risk factor for cardiovascular disease in subjects with abdominal obesity. In the present study, we investigated the effects of intake of WP and dietary fiber from enzyme-treated wheat bran on other metabolic parameters of the metabolic syndrome. Methods The study was a 12-week, double-blind, randomized, controlled, parallel intervention study. We randomized 73 subjects with abdominal obesity to 1 of 4 iso-energetic dietary interventions: 60 g per day of either WP hydrolysate or maltodextrin (MD) combined with high-fiber (HiFi; 30 g dietary fiber/day) or low-fiber (LoFi; 10 g dietary fiber/day) cereal products. We assessed changes in insulin sensitivity, gut hormones (GLP-1, GLP-2, GIP, and peptide YY), body composition, 24-h BP, resting energy expenditure and respiratory exchange ratio (RER), and appetite. Results Sixty-five subjects completed the trial. Subjective hunger ratings were lower after 12 weeks of WP compared with MD, independent of fiber content ( P = 0.02). We found no effects on ratings of satiety, fullness or prospective food consumption for either of the interventions. Intake of WP combined with LoFi increased the postprandial peptide YY response. There were no effects of WP or fiber on insulin sensitivity, body composition, energy expenditure, incretins, or 24-h BP. Conclusions WP consumption for 12 weeks reduced subjective ratings of hunger in subjects with abdominal obesity. Neither WP nor dietary fiber from wheat bran affected insulin sensitivity, 24-h BP, gut hormone responses, body composition, or energy expenditure compared with MD and low dietary fiber.